2021
DOI: 10.4236/ajibm.2021.116046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Access to Credit on the Sustainability of Small and Medium Sized Enterprises in Cameroon

Abstract: This paper aims at evaluating the major determinants of access to credit and their impact on the sustainability of SMEs in Cameroon using the 2016 World Bank enterprise survey. The probit model and linear regression model were used and the results show that collateral security, experience, interest rates, corruption and size of loan are the major determinants of access to credit and access to credit has a positive impact on the sustainability of SMEs in Cameroon. From the results, we can recommend the governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Similarly, has shown that education, household size, association member, experience and region are variables affecting access to credit while Langat (2013) confirmed that access to credit depended on credit standards, assess return on credit, evaluate risk on loan to farm and transaction cost. In addition, size of credit, duration of credit, number of credits obtained, usage of the credit, savings, collateral security, interest rate also act as important components that influence access to credit (Bin 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, has shown that education, household size, association member, experience and region are variables affecting access to credit while Langat (2013) confirmed that access to credit depended on credit standards, assess return on credit, evaluate risk on loan to farm and transaction cost. In addition, size of credit, duration of credit, number of credits obtained, usage of the credit, savings, collateral security, interest rate also act as important components that influence access to credit (Bin 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…His findings suggest that microfinance institutions have not been able to perform their business effectively because of capitalization. Similarly, Bin (2021) evaluates the major components of access to credit and their effects on the sustainability of SMEs in Cameroon by using the probit model and linear regression model with factors such as experience, interest rate, collateral security, corruption and size of loan. Assogba et al (2017) used the Logit model to conduct an analysis on the factors affecting farmers' access to credit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Cameroon, Djoumessi et al (2018) reported the significant role of access to agricultural extension services in influencing credit access. This is not mentioned by Bin et al (2021), who rather noted the role of corruption and loan size in inhibiting credit access.…”
Section: Review Of the Determinants Of Microcredit Accessmentioning
confidence: 93%
“…The high interest rate constraint was reported by 78% of nonbeneficiary rice farmers and only 15% of beneficiaries. However, it is possible that increased loan costs could be embedded in corrupt practices, which are rampant in financial transactions in Cameroon (Bin et al, 2021). This aspect, however, requires further research.…”
Section: Determinants Of Access To Agricultural Creditmentioning
confidence: 99%
See 1 more Smart Citation